O catador de materiais recicláveis no município de Ponta Grossa, Paraná: Perspectivas e necessidade de intervenção numa sociedade desigual - Rolim de Moura, Reidy; Dutra Szul, Karoline; Sene, Thais Sanson (Revista Desenvolvimento Social, 2021)
Public social policy is one of the pillars of the State and focuses on the provision of resources for redistributive actions that enable the means of subsistence capable of achieving and guaranteeing minimum equity in society. In this perspective, the present work seeks to bring a reflection about the application of the National Solid Waste Policy (PNRS) in the municipality of Ponta Grossa / PR in relation to the recyclable material collectors of the Rei do Pet Recyclers Association (ARREP). From a bibliographic and documentary review, with the collection of data in the banks of the Municipality of Ponta Grossa-PR and the application of a semi-structured questionnaire to ARREP associates, the confrontation of such data with the PNRS criteria was food security, access to social benefits and the municipal service network, which demonstrated as a result the vulnerability of members and how the application of PNRS is still fragile and disjointed in the municipality of Ponta Grossa-PR, as waste pickers still face primary difficulties, as the low income from the sale of materials and the absence of autonomy of the association vis-à-vis the government, which hinder full access to rights and citizenship.